2015
DOI: 10.1007/s12029-015-9789-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expanding Metallic Stents (SEMS) in Left-Sided Colonic Cancer—a Cancer Center Experience

Abstract: SEMS insertion for left-sided malignant colonic obstruction is a safe and effective procedure when used either as a bridge to surgery or with palliative intent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“… 7 , 12 Metallic stents, which have traditionally been used for palliation, now are recommended as a bridge to surgery for resectable obstructing colorectal tumours. 4 , 13 A meta-analysis by Allievi et al . 7 compared the use of stents with emergency surgery and found that use of the former was associated with a shorter hospital stay, helped to convert emergency to elective surgery, increased the likelihood of primary anastomosis, avoided surgery prior to diagnosis or staging, and was associated with better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 12 Metallic stents, which have traditionally been used for palliation, now are recommended as a bridge to surgery for resectable obstructing colorectal tumours. 4 , 13 A meta-analysis by Allievi et al . 7 compared the use of stents with emergency surgery and found that use of the former was associated with a shorter hospital stay, helped to convert emergency to elective surgery, increased the likelihood of primary anastomosis, avoided surgery prior to diagnosis or staging, and was associated with better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The most common and feared complication of SEMS insertion is local perforation, an event that has been reported to occur in the literature at a rate of 4%‐13% 22,23 . We reported a 9% rate of this complication in our series of patients, and found a nonsignificant, but positive, association between its occurrence and serum low haemoglobin levels: such an association might be explained by the fact that low haemoglobin concentration in the circulation is a hallmark of poor well‐being of patients, which in turn is usually a predisposing factor for any complication.…”
Section: Discussionmentioning
confidence: 99%
“…164 With respect to colonic SEMS, a large prospective series of 513 patients and 6 retrospective studies found the risk of clinically relevant haemorrhage within 7 days to be 0%. [165][166][167][168][169][170][171][172][173][174] A systematic review identifying 40 studies on SEMS for the management of emergency malignant large bowel obstruction identified 9 studies reporting on clinical relevant bleeding which occurred in 0.5% (8 out of 1474 patients). 175 We have considered endoscopic stenting at all sites in the GI tract to be low risk for haemorrhage within 7 days.…”
Section: Endoscopic Stentingmentioning
confidence: 99%